ANALYSIS OF DISTRIBUTION OF PRIME NUMBERS USING RIEMANN ZETA FUNCTION - Pavićević, Krsto (Matematichki Bilten, 2007)
The subject of this work is relation between Riemann zeta function and Prime Number Theorem which is the fundamental theorem for the subject of distribution of prime numbers.In order to make this work completed apart from original lemma [4] some already existing results relating to this matter are added as well.